The impact of vitamin D supplementation on hypertension: a literature review - Bielecka, Larysa (Journal of Education, Health and Sport, 2024)
Introduction Hypertension is one of the most common chronic diseases, and its prevalence continues to rise. Among the lesser-known factors contributing to the increased incidence of hypertension is vitamin D deficiency. Vitamin D, primarily known for its role in calcium and phosphate metabolism, has been implicated as one of the factors influencing cardiovascular function. Aim of the study The objective of this review is to analyze the current literature regarding the impact of vitamin D supplementation on blood pressure levels. Materials and Methods This review incorporates literature from the PubMed database, which was searched using the keywords "hypertension" and "vitamin D." Randomized controlled trials published between 2020 and 2024 were included. Results The literature review reveals various aspects of the relationship between vitamin D supplementation and blood pressure regulation. Hypertension remains one of the most prevalent chronic diseases, with its frequency consistently rising. Despite the development of new treatment methods, many patients still fail to achieve effective blood pressure control, posing a significant challenge to healthcare. Increasing evidence suggests that vitamin D may play a role in regulating blood pressure, which is particularly relevant given the widespread deficiency of this vitamin in global populations. Vitamin D deficiency is a common issue affecting a substantial portion of society, making the topic of supplementation and its potential effects even more urgent. Conclusion There is evidence to suggest potential benefits of vitamin D supplementation on blood pressure regulation, although the study results are inconclusive and do not yet support definitive clinical recommendations.